Opsarius putaoensis, a new species of subfamily Danioninae (Actinopterygii, Cyprinidae) from the Irrawaddy River basin in northern Myanmar - Qin, Tao; Maung, Kyaw Win; Chen, Xiao-Yong (Zootaxa, 2019)
Opsarius putaoensis, new species, is described from the Mali Hka River, a tributary of the Irrawaddy River in northern Myanmar. For convenience of identification, Opsarius sensu Rainboth (1991) in Southeast Asia and India can be divided into two species groups based on the number of anal-fin rays: (1) the O. gatensis species group with more than 12 branched anal-fin rays, and (2) the O. barna species group with fewer than 11 branched anal-fin rays. The remaining species of the O. barna species group can be divided into two species subgroups by the presence or absence of barbels: (1) the O. chatricensis species subgroup without barbels, and (2) the O. barnoides species subgroup with one or two pairs of barbels. Opsarius putaoensis sp. nov. is a member of the O. chatricensis species subgroup together with O. chatricensis, O. arunachalensis, and O. barna. Opsarius putaoensis is most similar to O. chatricensis in overall appearance, including the number of vertical bars and color pattern, but it differs from O. chatricensis by the following characters: insertion of dorsal not reaching posterior end of pelvic fin base vs. reaching, vertical bars 6−7 vs. 7−8, vertical bars extending to the lateral line vs. not, branched anal-fin rays 9 vs. 10, branched pelvic-fin rays 7 vs. 8, branched pectoral-fin rays 12, rarely 11 vs. 11, circumpeduncular scales 12 vs. 14, and scale rows between dorsal-fin origin and lateral line 7−8 vs. 6. It is distinguished from all other species of the genus Opsarius by a combination of the following characters: barbels absent, dentary with parallel rows of tubercles, snout much shorter than eye diameter, mouth gape below anterior edge of orbit, body deep with depth 25.6−33.3% SL, pectoral and pelvic axial scales lobate, lateral line completely perforated with 35−38 scales, scale rows between dorsal-fin origin and lateral line 7−8, predorsal scales 15, circumpeduncular scales 12, branched dorsal-fin rays 7, branched anal-fin rays 9, branched pelvic-fin rays 7, insertion of dorsal not reaching pelvic-fin base, body with 6−7 vertical bars, extending to lateral line, and distal edge of dorsal fin black.